An Empirical Analysis of Household Debt Behavior Determinants - Herispon, Herispon (Economics and Finance in Indonesia, 2019)
This study identifies the determinants of debt behaviors and their effects on household consumption. WeÂ surveyed households in Riau, particularly in Pekanbaru and its neighboring areas, using purposive samplingÂ and collected 390 useable responses. Our findings show that of the ten determinants considered, debtÂ behavior can be explained by five determinants: (i) imitated lifestyle and consumerism, (ii) ability to manageÂ money from debt, (iii) effects of promotion on the internet and visual media, (iv) monthly income, and (v)Â increasing household expenses and dependants. Implications of the findings are discussed.